Genetic diversity, correlation and path coefficient analysis of rajma bean (Phaseolus vulgaris) landraces in low altitude of Nagaland - THIRUGNANAVEL, A; DEKA, BIDYUT C; KUMAR, RAKESH; RANGNAMEI, LILY; MEYASE, MEGHOKHONO (The Indian Journal of Agricultural Sciences, 2019)
Thirty two rajma beans (Phaseolus vulgaris L.) landraces have been evaluated for 17 traits to study the genetic variability, correlations and direct and indirect effect of characters on yield. Results showed that wide range of variations were observed for all 17 traits among the landraces. Moderate to high level of GCV and PCV and high level of heritability were observed for all the traits. PCV was slightly higher than GCV, but the difference was insignificant. The traits such as plant height, number of seeds/plant, number of pods/plant, test weight and seed yield recorded high level of GCV, PCV and heritability. Correlation results showed that seed yield had positive and high correlation (p